DESAIN LANSKAP WISDESAIN LANSKAP WISATA REKREASI OELUAN KABUPATEN TIMOR TENGAH UTARAATA REKREASI OELUAN KABUPATEN TIMOR TENGAH UTARA - Funan, Nemesius; Setyabudi, Irawan; Alfian, Rizki (Fakultas Pertanian, 2019)
Oeluan tourism object as one of the natural attractions and swimming pools in North Central Timor Regency is currently a reliable tourist asset because it has a future orientation to increase regional income. For this reason, it needs to be supported by the availability of tourism products including tourist attractions, transportation, service facilities, and information and promotions regarding the existence of tourist objects. The purpose of this study was to create an Oeluan recreational tourism landscape design in North Central Timor Regency. The stages of landscape architecture design start from identifying physical / biophysical aspects, analysis, proggramatic concepts and initial design, and design development. Oeluan recreational tourism landscape design uses the concept of back to nature with a blend of local culture in North Central Timor Regency. This is in accordance with the conditions of Oeluan tourism object, because most of the existing facilities are not compatible with nature or environmentally friendly, by utilizing the availability of natural materials around the site. So as to be able to rehabilitate the natural condition of the forest, as well as integrate the socio-cultural values of the community so that environmental conditions can be maintained and the creation of harmony between human life and the surrounding environment. The results obtained were in the form of Oeluan recreational tourism landscape design in North Central Timor Regency. The conclusion of this study is to recommend a recreational tourism landscape design that can meet the needs of visitors, while maintaining the preservation of forest ecosystems with spatial planning, activities, circulation, facilities and utilities, as well as analyzing the environment inside and outside the site. In addition, local people are involved in tourist attractions, become facilitators, guides, performing arts and culture, with the aim of increasing the economy of local communities. Obyek wisata Oeluan sebagai salah satu obyek wisata alam dan kolam renang di Kabupaten Timor Tengah Utara saat ini menjadi aset wisata yang dapat diandalkan karena memiliki orientasi kedepan menambah pendapatan daerah. Untuk itu perlu didukung dengan ketersediaan produk wisata diantaranya atraksi wisata, transportasi, fasilitas pelayanan, serta informasi dan promosi mengenai keberadaan objek wisata. Tujuan dari penelitian ini adalah membuat desain lanskap wisata rekreasi Oeluan Kabupaten Timor Tengah Utara. Tahapan desain arsitektur lanskap dimulai dari mengidentifikasi aspek fisik/biofisik, analisis, konsep proggramatik dan desain awal, serta pengembangan desain. Desain lanskap obyek wisata rekreasi Oeluan menggunakan konsep back to nature dengan perpaduan budaya lokal Kabupaten Timor Tengah Utara. Hal ini sesuai dengan kondisi keadaan obyek wisata Oeluan, karena sebagian besar fasilitas yang ada saat ini belum serasi dengan alam atau ramah lingkungan, dengan memanfaatkan ketersediaan material alami yang terdapat disekitar tapak. Sehingga mampu merehabilitasi kondisi alami hutan, serta memadukan nilai sosial budaya masyarakat agar dapat terpeliharanya kondisi lingkungan hidup maupun terciptanya keharmonisan antara kehidupan manusia dengan alam sekitarnya. Hasil yang diperoleh berupa rancangan lanskap wisata rekreasi Oeluan Kabupaten Timor Tengah Utara. Kesimpulan dari penelitian ini adalah merekomendasikan desain lanskap wisata rekreasi yang dapat mencukupi kebutuhan pengguna, serta tetap memperhatikan kelestarian ekosistem hutan dengan perencanaan tata ruang, aktifitas, sirkulasi, fasilitas, dan utilitas, maupun analisis lingkungan didalam maupun diluar tapak. Selain itu, masyarakat lokal dilibatkan pada atraksi wisata, menjadi fasilitator, pemandu, pertunjukan seni dan budaya, dengan maksud dapat meningkatkan perekonomian masyarakat lokal.